Розвиток професійної ідентичності майбутніх правоохоронців шляхом соціально- психологічного тренінгу - Макарова, О. П.; Makarova, O. P. (Вісник Національного університету оборони України. - 2014. - Вип. 6(43). - С. 317-321, 2014)
В статті розглянуто методологічні основи проведення соціально - психологічного тренінгу розвитку професійної ідентичності. Визначено його структуру, специфіку та основні блоки. Соціально – психологічний тренінг розглядається автором , як активна форма соціально – психологічного навчання, що є цілісною психолого – педагогічною системою, яка здатна допомагати курсантам у пізнанні себе, своїх умінь та навичок. Розглянуто структурно-функціональні особливості соціально-психологічного тренінгу розвитку професійної ідентичності майбутніх правоохоронців.

The author analyzed the methodological ground for conducting the socio-psychological training for the professional identity development. The structure, specific features and the main directions were defined. The analysis of the professional identity structure was conducted. The mentioned analysis includes: the connection of cognitive, value and behavioural characteristics of the personality, which ensure the orientation in the professional field; to forecast possible consequences of the professional choice and the prospects of the professional growth. The socio-psychological training is considered as the active form of the socio-psychological education, which is the comprehensive psycho-pedagogical system, that can help the students in the process of the self-actualization. The author analyzed the functional features of the socio-psychological training of the professional identity of the future law-enforcement officers.

В статье рассмотрены методологические основы проведения социально – психологического тренинга развития профессиональной идентичности. Определена его структура, специфика и основные блоки. Социально – психологический тренинг рассматривается автором, как активная форма социально – психологического обучения, что является целостной психолого – педагогической системой, которая может помочь курсантам в познании себя, своих умений и навыков. Рассмотрены структурно – функциональные особенности социально - психологического тренинга развития профессиональной идентичности бедующих правоохранителей.
Development of professional identity of future pravoohorontsіvп by the way of the socially psychological training
Keywords: соціально–психологічний тренінг; професійна ідентичність; майбутні правоохоронці; професійне самовизначення; професійна діяльність; psychological training; professional identity; future law enforcement officers; professional self-actualization; professional activity; социально – психологический тренинг; профессиональная идентичность; будущие правоохранители; профессиональное самоопределение; профессиональная деятельность